THE EFFECTIVENESS OF HEALTH EDUCATION ON SANDSTONE CRAFTSMAN’S KNOWLEDGE AND ATTITUDE ABOUT OCCUPATIONAL LUNG DISEASE PREVENTION - Nima Eka Nur Rahmania; Ellyza Setya Maryiantari (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: The activity of the sandstone home industry has a high risk of occupational lung disease, namely silicosis with exposure to respirable dust that contains silica below 2.5 microns. The craftsmen of the sandstone home industry must have good knowledge and attitudes in order to apply occupational lung disease prevention. Objectives: The purpose of this research was to determine the effectiveness of health education on the level of knowledge and attitude of sandstone craftsmen about occupational lung disease prevention. Methods: The research design used in this study was pre-experimental with a one-group pre-posttest design approach. This research was conducted in the sandstone home industry, Gamping Village, Tulungagung from June until July 2021. The sampling technique was total sampling with a number of samples were 20 respondents. This study used health education materials about occupational lung disease prevention for the treatment given and a modified questionnaire from Rahmania (2011) with a significance of validity for the knowledge and attitude instrument were α < 0.05 and Cronbach Alpha values ​​for knowledge and attitudes respectively 0.680 and 0.70. This research was conducted by providing health education to respondents about occupational lung disease prevention. Before and after the health education was carried out, the researcher conducted a pre-posttest to measure and evaluate the respondents' level of knowledge and attitude about occupational lung disease prevention. The statistical test carried out in this study was the Wilcoxon Signed Rank Test with a significant level α < 0.05. Results: Based on the data analysis by using the Wilcoxon Signed Rank Test, there was an effect of health education about occupational lung disease prevention on the level of sandstone craftsmen’s knowledge (p-value = 0.000) and attitude (p-value = 0.000). Conclusion: It is important to provide health education about the health effect of sandstone dust and the prevention so that craftsmen have a good knowledge and attitudes in implementing to prevent of occupational lung diseases. Health education or counseling needs to be provided by health workers periodically.